Analisis Prediksi Financial Distress Menggunakan Model Altman Z-Score Modifikasi dengan Pendekatan Benchmarking pada PT Gudang Garam Tbk - Wilda Komala Viani; Dwi Eko Waluyo; Yenny Ernitawati; Ariati Anomsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to evaluate PT Gudang Garam Tbk's financial situation and use the Modified Altman Z-Score model to forecast future financial difficulties. In addition, this study conducts a benchmarking analysis with peer companies in the tobacco industry listed on the Indonesia Stock Exchange (IDX) to determine the company’s relative position. Using financial statement data from 2019 to 2025, this study uses a quantitative descriptive methodology. To strengthen the analysis, a difference test was conducted using the Wilcoxon Signed Rank Test due to the non-normal distribution of the data. The results indicate that PT Gudang Garam Tbk consistently remains in the “healthy” category, with Z-Score values above the safe threshold (>2.6), suggesting no indication of financial distress. The difference test results show no significant difference between PT Gudang Garam Tbk and PT HM Sampoerna Tbk as well as PT Wismilak Inti Makmur Tbk, while a significant difference is found when compared to PT Indonesian Tobacco Tbk. These findings suggest that PT Gudang Garam Tbk maintains a relatively stable and competitive financial position within the tobacco industry.